Treatment of amyotrophic lateral sclerosis patients by autologous bone marrow-derived hematopoietic stem cell transplantation: a 1-year follow-up - (:unkn) unknown (ELSEVIER SCI LTD, 2009)
Background Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by progressive loss of spinal cord and cortical motoneurons. Despite improved understanding of the mechanisms underlying ALS, in clinical practice the management of ALS remains essentially supportive and focused on symptom relief. However, over the past few years stem cell research has expanded greatly as a tool for developing potential new therapies for treating incurable neurodegenerative diseases. Methods Thirteen patients with sporadic amyotrophic lateral sclerosis (SALS) were included in this study, and bone marrow (BM)-derived hematopoietic progenitor stem cells were used. We selected patients with bulbar involvement and severe loss of movement. Our aim was to put the stem cells into the end of the brain stem and at the beginning of the spinal cord because the blood-brain barrier is intact in ALS and this region was the most affected part in our patients. Under general anesthesia, a total laminectomy was performed at the C1-C2 level. Stem cells were injected to the anterior part of the spinal cord. Results During the follow-up of 1 year after stem cell implantation, nine patients became much better compared with their pre-operative status, confirmed by electro neuro myography (ENMG). One patient was stable without any decline or improvement in his status. Three patients died 1.5, 2 and 9 months, respectively, after stem cell therapy as a result of lung infection and myocardial infarction (MI). Discussion These results show that stem cell therapy is a safe, effective and promising treatment for ALS patients.
Keywords: amyotrophic lateral sclerosis; bone marrow; repair; stem cell; THERAPY; MECHANISMS